Rekomendasi Pengelolaan Kawasan Cagar Budaya Pelabuhan Boom dan Shipwreck di Pulau Bawean, Kabupaten Gresik - Dhony, Muslim Dimas Khoiru; Safitri, Laksmi Eko (Department of Archaeology, Faculty of Cultural Sciences, Universitas Gadjah Mada, 2025)
The Boom Harbor Cultural Heritage Area and the shipwrecks off Bawean Island are significant cultural heritages that require sustainable management planning. This study aims to provide a concise overview of the management strategies for developing and utilizing the Boom Harbor Cultural Heritage Area and the shipwrecks. Data analyzed stem from the Decree of the Regent of Gresik No. 028/478/HK/437.12/2020, which establishes the Boom Harbor Area, and the cultural heritage recommendation file document number 432-3/009/TACB-Kab.Gresik/05/12/2016, which pertains to the shipwrecks. These documents highlight that these sites possess considerable historical, scientific, and cultural value. The planning strategy follows the guidelines outlined in the 2011 Historic Urban Landscape Recommendation (UNESCO), which identifies four key